Pengaruh Cara Pengeringan dengan Microwave terhadap Perolehan Kadar Senyawa Fenolat dan Aktivitas Antioksidan dari Daun Dewa (Gynura pseudochina (Lour.), Merr.) - Zet Rizal; Deswati Deswati; Harrizul Rivai (Jurnal Farmasi Higea, 2009)
The research about the effect of microwave drying methods on content of phenolic compounds and antioxidant activity of Gynura pseudochina,(Lour.) Merr. have been done. The determination of phenolic compounds was carried out according to Folin-Ciocalteu method and antioxidant activity was evaluated by DPPH method, calculated as gallic acid equivalent (GAE). The research showed that the highest phenolic compounds and the strongest antioxidant activity obtained by microwave drying method compared by air drying method. The phenolic compounds each gram sample by using microwave drying is 1.673 mg phenolic compounds and antioxidant activities were calculated as the IC50 at concentration 2.876 mg/mL.